The effects of loaded plyometric exercise during warm-up on subsequent sprint performance in collegiate track athletes: A randomized trial - Tomlinson, K. A.; Hansen, K.; Helzer, D.; Lewis, Z. H.; Leyva, W. D.; McCauley, M.; Pritchard, W.; Silvestri, E.; Quila, M.; Yi, M.; Jo, E. (Sports, 2020)
Prior evidence demonstrates the efficacy by which plyometric activities during warm-up conditions augment the subsequent performance in power-centric exercise. We investigated the acute effects of loaded jump squats incorporated into a standard sprinters` warm-up protocol on subsequent sprint performance in collegiate track athletes. Sprint times of 22 male and female collegiate track athletes were measured in 10-m intervals during a 30-m sprint trial following a standard sprinters` warm-up routine with or without plyometric exercise. Subjects were tested on two separate occasions, once with loaded jump squats as the experimental treatment (two sets of eight jumps, load = 13% bodyweight) (PLYO) and once with time-equated rest as the control treatment (CON). Treatments were implemented following a standard sprinters` warm-up routine familiar to the subjects. A dependent T-test was used for comparison of sprint interval times between conditions with a significant effect indicated by a p-value < 0.05. Sprint time did not differ between CON vs. PLYO at the 10 m (PLYO = 1.90 ± 0.12 s vs. CON = 1.90 ± 0.11 s, p = 0.66), 20 m (PLYO = 3.16 ± 0.21 s vs. CON = 3.15 ± 0.19 s, p = 0.53), and 30 m (PLYO = 4.32 ± 0.32 s vs. CON = 4.31 ± 0.28 s, p = 0.61) intervals. There was no interaction between treatment and sex, sex-specific ranking (above vs. below sex-specific mean), or sprint event (short vs. short-long vs. long) for 10 m, 20 m, or 30-m interval sprint times. At least within the limits of the current investigation, no evidence was provided to suggest that jump squats loaded at 13% bodyweight are an effective means to acutely potentiate sprint performance in collegiate track athletes. However, a further examination of responders indicates that the present loaded jump squat protocol may preferentially potentiate sprint performance in faster male athletes.